Implementation of Islamic Business Ethics Principles in Building Consumer Loyalty: A Qualitative Study of Culinary Sector MSMEs in Surabaya - Aditya, Anggy (CV. Megantara Abdi Nusa, 2025)
The application of Islamic business ethics is crucial for sustaining competitiveness and fostering consumer loyalty in culinary MSMEs, particularly in metropolitan cities like Surabaya, where market complexity and consumer heterogeneity are high. This study aims to explore how Islamic business ethics are implemented in culinary MSMEs and their impact on consumer loyalty. A descriptive qualitative approach was employed, involving in-depth interviews, observations, and documentation studies with 5 MSME owners, 5 employees, and 10 regular consumers, using purposive and snowball sampling to achieve data saturation. Data were analyzed using the Miles, Huberman, and Saldaña model, supported by triangulation techniques for validity. The findings indicate that honesty, trustworthiness, fairness, social responsibility, and the prohibition of usury and fraud are consistently applied, positively influencing consumer loyalty, reflected in repeat visits, word-of-mouth recommendations, satisfaction, and emotional attachment. Implementation is supported by owner awareness, consumer appreciation, and flexible business scale, while resource constraints, competitive pressures, and varying understanding among non-Muslim consumers act as barriers. These results suggest that Islamic business ethics function not only as moral guidelines but also as effective strategies to build trust, emotional attachment, and long-term loyalty, providing practical and theoretical guidance for sustainable MSME development.